USE OF INNOVATIVE DESIGN TECHNOLOGIES TO CREATE A COMFORTABLE WORKING SPACE IN IT COMPANY - Pylypenko, Natallia; Khlyzova, Polina (Theory and practice of design, 2023)
The article aims to demonstrate the importance and apply methods of creating a comfortable environment for work in office buildings of IT companies, as well as to show the impact of a quality and ergonomic environment on the work results of a team that has the opportunity to work, undergo training and rest in an environment designed in accordance with every person needs everyone. Purpose. Analysis of modern aspects of creating a comfortable working environment for IT companies, such as planning, lighting, furniture, color, acoustics and ventilation with the help of innovative design technologies, such as virtual reality, biophilic design, smart materials and interactive systems, can help improve the quality and functionality of the workspace. The methodology is based on a systematic approach, which includes the analysis of the interiors and the suitability of the premises of the world’s best IT companies, which provide the highest quality work results from workers by creating favorable working conditions for them and filling the space of the place for the components of psychological and physical comfort. Results. Determining the impact of a quality and ergonomic environment on the performance of a team that has the opportunity to work, train and relax in an environment designed to meet all the needs of each person. Scientific novelty. The article presents current topics of the quality and level of comfort of working environments and taking into account the psychological aspect in the planning of space for employees. Practical relevance. The results of the research can be used in the development of design – projects using modern design technologies in office premises to improve working conditions, increase the comfort of the working space to maximize the motivation and productivity of each employee, taking into account such approaches as the adaptability of the workplace to the needs of each employee, the creation of inspiring interiors, opportunities for learning and research within the framework of the workplace, research into ways of rest and individualization of space for each individual employee.